2021
DOI: 10.3389/fcell.2021.648209
|View full text |Cite|
|
Sign up to set email alerts
|

Melatonin Modulates Lipid Metabolism in Porcine Cumulus–Oocyte Complex via Its Receptors

Abstract: Lipid is a crucial energy resource for mammalian oocyte. Melatonin could benefit the maturation of porcine oocyte in vitro, but the related mechanism is not elucidated yet. In the current study, methods to monitor lipid metabolism in single live oocytes were firstly established using probes (Lipi-Blue and Lipi-Green). It was observed that both lipid biogenesis and lipolysis occurred in maturing oocyte, but the general level of lipids dropped. Then maturing oocytes stained with probes were treated with melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This finding suggested that an increase in cardiac fat utilization is the direct effect of melatonin itself, rather than a consequence of melatonin‐induced amelioration of ventricular hypertrophy. Consistent with our findings, a melatonin‐induced increase in fatty acid oxidation was also demonstrated in preadipocytes and oocytes isolated from healthy pigs 47,48 . Under physiologic conditions, fat is a major and critical substrate for ATP production in the normal heart 7 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding suggested that an increase in cardiac fat utilization is the direct effect of melatonin itself, rather than a consequence of melatonin‐induced amelioration of ventricular hypertrophy. Consistent with our findings, a melatonin‐induced increase in fatty acid oxidation was also demonstrated in preadipocytes and oocytes isolated from healthy pigs 47,48 . Under physiologic conditions, fat is a major and critical substrate for ATP production in the normal heart 7 .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, a melatonin-induced increase in fatty acid oxidation was also demonstrated in preadipocytes and oocytes isolated from healthy pigs. 47,48 Under physiologic conditions, fat is a major and critical substrate for ATP production in the normal heart. 7 Hence, an enhancement of cardiac fatty acid oxidation is likely to promote favorable cardiac function and delay the progression of heart failure.…”
Section: Doxorubicin Increased Mitochondrial Oxidative Stress In Embr...mentioning
confidence: 99%
“…On the other hand, melatonin is known as an antioxidant or free-radical scavenger by reducing the excessive production of ROS, thereby protecting against cardiac dysfunction under hypoxia (Poeggeler et al, 1994;Gonzaléz-Candia et al, 2021). Previous studies have suggested that adding melatonin (MT) for in vitro maturation improves the developmental competence of oocytes by scavenging reactive oxygen species (ROS) through melatonin receptor 2 in the cumulus-oocyte complex (Kim et al, 2020;Zhu et al, 2021). Melatonin acts on the Nrf2 signalling pathway through its receptors to induce the expression of downstream antioxidant proteins, thereby reducing the accumulation of ROS and enhancing the in vitro development potential of oocytes under stress (Guo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The simplified experimental flow of our study design ( Figure 1 a) supports the field of mammalian reproduction by providing a framework for controlled experiments, such as testing the efficacy of unknown chemicals on mammalian oocyte maturation without FF or serum. However, numerous studies have been published regarding the key factors of pFF [ 16 , 19 , 20 , 21 ] and tests for unknown chemicals during mammalian oocyte maturation or embryo development with or without defined media [ 22 , 23 , 24 , 25 ]. Although studies using defined media may be suitable for testing unknown chemicals, many have shown poor oocyte development.…”
Section: Discussionmentioning
confidence: 99%